Statistical Assessment of the Budget Management Effectiveness When Drawing Up, Reviewing and Approving the State Budget - Melnychuk, N. Yu.; Parfentseva N. О.; Melnychuk І. O. (Statistics of Ukraine, 2019)
Theoretical and methodological foundations for evaluating the effectiveness of managing the budget process at its initial stage are deepened, views of various experts on the management effectiveness when drawing up, reviewing the draft law and adopting it are considered. It is substantiated that in recent years the procedure and terms of submitting the draft and adopting the Law of Ukraine “On the State Budget of Ukraine” have been repeatedly violated. The necessity to increase the budget management effectiveness at the first stage of the budget process is proved. The questionnaire of the public poll is developed, on the basis of which the evaluation of the management effectiveness when drawing up, reviewing of the draft Law of Ukraine “On the State Budget of Ukraine” and its adoption is made.Indicators that allow characterizing the budget management effectiveness when drawing up, reviewing and approving the state budget are proposed. The proposed calculations are based on the assertion that the efficiency is a component of the management effectiveness. The following are pointed out: index of timely submission of the management object; index of timely fixation of the management object; index of timely acceptance of the management object. Introduction of these indicators allows characterizing the management effectiveness on the tasks fulfillment set for the government concerning the compliance with the budget legislation and the basics of the state budget policy for the next reporting period, approved by the Verkhovna Rada of Ukraine when drafting the State Budget Law. Using the proposed indexes of the management effectiveness, an integral index of the budget management effectiveness at the first stage of the budget process is calculated. It is argued that in 2004 there was a high efficiency of the budget management at the first stage of the budget process; in 2006, 2012, 2014, 2017 and 2018, the efficiency was average, and in 2010 and 2013, its efficiency was below average. The integral index of the budget management effectiveness at the first stage of the budget process was in the critical efficiency zone in 2005, 2007, 2008, 2009, 2011, 2015, and 2016.It is proved that there is an average correlation between the integral index of the budget management effectiveness at the first stage of the budget process and (i) the number of changes made to the draft law; (ii) real GDP growth rate.